Cournot competition on a network of markets and firms - Rahmi Ilkiliç (Fondazione Eni Enrico Mattei (FEEM), 2009)
Suppose markets and firms are connected in a bi-partite network, where firms can only supply to the markets they are connected to. Firms compete a la Cournot and decide how much to supply to each market they have a link with. We assume that markets have linear demand functions and firms have convex quadratic cost functions. We show there exists a unique equilibrium in any given network of firms and markets. We provide a formula which expresses the quantities at an equilibrium as a function of a network centrality measure.
Keywords: C62; C72; D85; L11; 330; Cournot Markets; Networks; Nash Equilibrium; Centrality Measures